Building Characteristics and Incompatible Land Uses as Drivers of Fire Disaster Risk - Falola, Olusegun Joseph; S.B. Agbola; A.M. Alabi (Indonesian Journal of Social and Environmental Issues (IJSEI), 2024)
Risk-based land use planning is regarded as a controlling tool for reducing environmental disasters in urban settlements. However, unsustainable land use practices allow building and infrastructural developments in fire disaster-risk areas. Losses to urban fires are largely dependent on building and land use characteristics across settlements. This paper examines the underlying characteristics that increase fire risks in urban buildings by analyzing the relationship between land use patterns, types of building use, and fire disaster risk in the metropolitan area of Ibadan, Nigeria. Data were collected through a field survey using a structured questionnaire supplemented by focus group discussion. A multistage sampling procedure was used to select 88 neighborhoods and 1,803 building occupants were selected using systematic random sampling. Findings indicate incompatible land use developments in many areas of the city. The study revealed that one out of five buildings were not accessible to fire-fighting vehicles owing to inadequate road widths (43.7%) and pot-holes (39.8%). One out of seven buildings (14.1%) had no water supply. About 10% of the buildings had emergency doors on permanent lock. About half of the building occupants relied on power supply sources that increased risks of fire occurrence (52%) and 49.4% used unsustainable waste disposal methods that threatened fire safety. The paper concluded that land use attributes, such as accessibility, compatibility of uses, water supply sources, sources of electricity supply and solid waste disposal method, and building characteristics, such as burglar proofs, nature of entrance/exit, type of lighting fuel are factors that are relevant in fire disaster risk analysis.